No Pain Labor & Delivery: A Global Health Initiative's Impact on Clinical Outcomes in China. (June 2016) - Hu, Ling-Qun; Flood, Pamela; Li, Yunping; Tao, Weike; Zhao, Peishan; Xia, Yun; Pian-Smith, May C.; Stellaccio, Francis S.; Ouanes, Jean-Pierre P.; Hu, Fengling; Wong, Cynthia A.
Abstract : The availability of labor analgesia is highly variable in the People's Republic of China. There are widespread misconceptions, by both parturients and health care providers, that labor epidural analgesia is harmful to mother and baby. Meanwhile, China has one of the highest cesarean delivery rates in the world, exceeding 50%. The goal of the nongovernmental No Pain Labor & Delivery (NPLD) is to facilitate sustainable increases in vaginal delivery rates by increasing access to safe neuraxial labor analgesia, thereby decreasing the cesarean delivery rate. NPLD was launched in 2008 with the stated goal of improving labor outcome in China by increasing the absolute labor epidural analgesia rate by 10%. NPLD established 10 training centers over a 10-year period. We hypothesized that increased availability of labor analgesia would result in reduced requests for cesarean delivery and better labor outcomes for mother and baby. Multidisciplinary teams of Western clinicians and support staff traveled to China for 8 to 10 days once a year. The approach involved establishing 24/7 obstetric anesthesia coverage in Chinese hospitals through education and modeling multidisciplinary approaches, including problem-based learning discussions, bedside teaching, daily debriefings, simulation training drills, and weekend conferences. As of November 2015, NPLD has engaged with 31 hospitals. At 24 of these sites, 24/7 obstetric anesthesia coverage has been established and labor epidural analgesia rates have exceeded 50%. Lower rates of cesarean delivery, episiotomy, postpartum blood transfusion, and better neonatal outcomes were documented in 3 impact studies comprising approximately 55, 000 deliveries. Changes in practice guidelines, medical policy, and billing codes have been implemented in conjunction with the modernization of perinatal practice that has occurred concurrently in China since the first NPLD trip in 2008.